Hubungan Pengetahuan dan Nilai Norma Sosial dengan Perilaku Konsumsi Buah dan Sayur pada Siswa-Siswi SD Wonolelo Pleret Bantul Yogyakarta - Isnaningsih, Tantiana; Khamid, Ahmad; Anggoro, Sarni (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2024)
The aim of the corelation between knowledge and social norm values ​​and fruit and vegetable consumption behavior among students at Wonolelo Pleret Elementary School, Bantul, Yogyakarta. This research is a descriptive quantitative analytical survey research using a cross sectional design with a sample size of 39 people. Univariate and bivariate data analysis used the chi square test (α=0.05). The research found that there was a corelation between nutritional knowledge and fruit and vegetable consumption behavior, namely 0.017, so there was a significant corelation between nutritional knowledge and fruit and vegetable consumption behavior among students at Wonolelo Pleret Elementary School, Bantul, Yogyakarta in 2018. There was a corelation between norms and values. -socio-cultural values ​​with fruit and vegetable consumption behavior is 0.005, so there is a significant corelation between socio-cultural norms and values ​​and fruit and vegetable consumption behavior among Wonolelo Elementary School students Pleret Bantul Yogyakarta . There is a corelation between knowledge and norms and socio-cultural values ​​with fruit and vegetable consumption behavior among students at SD Wonolelo Pleret Bantul Yogyakarta.